Mechanical Analysis Method of Cantilever Gearbox - Wang Jue; Song Shiyao; Zhang Rui (Jixie chuandong)
The cantilever gearbox and the traditional gearbox have great difference in the structure and the force condition. The resonance mechanical analysis method of traditional gearbox could not get the accurate fatigue position of the gearbox. Taking a type of shearer cutting unit cantilever gearbox as the research object,the statics analysis and local resonance analysis are used to analyze the mechanical characteristics under the internal incentive and cutting load external excitation. The statics analysis takes into account the influence of the axial force,eccentricity and the torque generated by the gear meshing force on the force state of the case. Based on the shearer cutting test,the local resonance analysis is carried out,and the frequency domain characteristics of the vibration signals of several typical cases are obtained,and compared with the natural characteristics of the box. The results show that high stress and large deformation are caused by low frequency impact（ quasi static load） and local resonance. Neglecting one of these factors will lead to inaccurate analysis of box fatigue. The research result is in good agreement with the engineering practice.